Impact of primary hyperidrosis on the quality of life of basic teachers (Research, Society and Development, 2021)
The objective of this study was to analyze the knowledge, prevalence and impact of Primary Hyperhidrosis on the quality of life of primary school teachers in private schools in the municipality of Aracaju/SE. Descriptive, exploratory research with a quantitative approach. Data collection started with the application of a questionnaire of prior knowledge about Primary Hyperhidrosis and then a lecture on the disease was held. After explaining the topic, the teachers answered three other questionnaires, which were: Diagnostic Criteria; Hyperhidrosis Disease Severity Scale; and Quality of Life - Hyperhidrosis. Research approved by the Research Ethics Committee of Universidade Tiradentes (3.266.630). The prevalence of PH was 8.2% in the study, where 78.3% were female, 49.2% in the age group 31 to 40 years old and 61.2% brown. The onset of the disease occurred between 15 and 20 years in 27.3%. 82.8% of teachers were unaware of HP. Grade 02 predominated in 36.4%. As for the anatomical site, 45.5% described the palmar and 45.5% the plantar as the main affected. The diagnosis of PH by a health professional was reported by 13.6% of teachers. Regarding quality of life, it was found that the total score of the domains ranged from 20 (excellent) to 75 (poor), with an average of 46.7 points, where 3 (13.6%) were classified as poor. Thus, acting in the dissemination of information about HP is essential to increase knowledge about this disease among professionals, students, parents and guardians.